2021
DOI: 10.3897/phytokeys.179.66312
|View full text |Cite
|
Sign up to set email alerts
|

Morphology of pollen in Ferula genus (Apiaceae)

Abstract: In this study, the pollen morphology of all Ferula species distributed throughout the country of Turkey was studied with light and scanning electron microscopy for the first time. The aim is to identify the pollen morphological characteristics of 23 Ferula species. The pollen is radially symmetrical, isopolar and tricolporate in all examined species. Pollen grains are prolate and perprolate with the polar axis ranging from 22.28 to 40.47 µm and the equatorial axis from 13.70 to 18.73 µm. Their polar shapes are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…The current results are in agreement to (De Leonardis, De Santis, Ferrauto, & Fichera, 2009) who determined similar wall ornamentation. In our current results A. burtii have regulate type of ornamentation which in consistent with the previous findings of Baser, Sagıroglu, Dogan, and Duman (2021) on other members of family Apiaceae. Similarly, B. falcatum subsp.…”
Section: Discussionsupporting
confidence: 93%
“…The current results are in agreement to (De Leonardis, De Santis, Ferrauto, & Fichera, 2009) who determined similar wall ornamentation. In our current results A. burtii have regulate type of ornamentation which in consistent with the previous findings of Baser, Sagıroglu, Dogan, and Duman (2021) on other members of family Apiaceae. Similarly, B. falcatum subsp.…”
Section: Discussionsupporting
confidence: 93%
“…In this study, the pollen morphology of 17 taxa (18 accessions) of the family Apiaceae (13 Daucus and 4 non-Daucus taxa) was determined, of which 13 taxa (11 Daucus and 2 non-Daucus) were examined for the first time. In all taxa, tricolporate and prolate-perprolate-shaped pollen were observed, which is a common feature of the pollen grains of Apiaceae [48][49][50][51][52].…”
Section: Discussionmentioning
confidence: 99%
“…We also compared the data included in PalDat for species of different genera belonging to the family Apiaceae that were also analyzed by SEM (50 species representing 31 genera) and verified that the pollen grains of most of these species are rugulate and perforate (or only rugulate/ perforate), suggesting strong homogeneity for this trait in Apiaceae. Nonetheless, outside PalDat, some other types of exine ornamentation in Apiaceae have also been reported in the literature, e.g., cerebroid, pertectate, and verrucate [50][51][52]55].…”
Section: Discussionmentioning
confidence: 99%
“…Although Apiaceae is known as a stenopalynous family, recent studies have shown that pollen traits (i.e. shape, aperture and ornamentation) could differ among species (Baldemir et al 2018, Baczyński et al 2021, Başer et al 2021). We thus decided to use light and scanning electron microscopy to conduct a comparative examination of the pollen grains of C. bulbosum , C. karsianum and C. posofianum .…”
Section: Introductionmentioning
confidence: 99%